Sacerdotes y tejedores en la provincia inka de Pachacamac - Cornejo, Miguel (Pontificia Universidad Católica del Perú. Fondo Editorial, 2002)
Investigaciones arqueológicas han comprobado que, durante el Periodo Intermedio Tardío y el Horizonte Tardío, algunos contextos funerarios son diagnósticos en la identificación de especialidades u oficios laborales. Esto puede demostrarse en la provincia inka de Pachacamac y en este artículo se intenta caracterizar algunos aspectos de dos grupos de especialistas identificados por el análisis arqueológico, apoyado por importantes y reveladoras informaciones etnohistóricas. Es interés del autor mostrar los resultados de sus investigaciones respecto a los sacerdotes y tejedores andinos.

Priests and Weavers in the Inka Province of PachacamacBy following the principle that offerings, accompanying the dead, can be used effectively to determine the former occupation the deceased, we can extend our knowledge of the social organisation of the Province of  Pachacamac. The meaning of offerings in terms of level of social status and occupation is interpreted by artifacts which probably belonged the deceased, including those which would include personal items and the tools of the trade, both of which would confirm what kind of social status the deceased enjoyed and what trade he or she pursued. This suits particularly well if the tools and other instruments for specific tasks show signs of wear and if there are half-finished products, such as textiles or nets. In this article I want to identify aspects concerning two specialists groups: the priests and weavers.
Keywords: Arqueología; Contextos Funerarios; Objetos Asociados; Periodo Intermedio Tardío; Horizonte Tardío; Identificación de Grupos Sociales; Archaeology; Funerary Contexts; Associated Objects; Late Intermediate Period; Late Horizon; Identification Of Social Groups; https://purl.org/pe-repo/ocde/ford#6.01.02